Formalization of the problem of synthesis and analysis of servicing technological systems - Мелкумян, В. Г. (Proceedings of National Aviation University, 2000)
Considered is one of the approaches to expert estimation of probable servicing market and servicing technological system with use of applied theory of add set of numbers